Constitutional Wrongs Without Remedies: Executive Official Immunity - Sheldon H. Nahmod (Washington University Law Quarterly, 1984)
Part I of this Article provides a retrospective which shows the development of section 1983 qualified immunity doctrine. In Part II, federal executive immunity, including the Court's emphasis on function and presidential immunity, is considered. Part III critically analyzes the Court's current approach to executive immunity, as reflected especially in Harlow v. Fitzgerald with its questionable reliance on cost-benefit analysis.
Keywords: Costs (Economics); Government liability; Privileges and immunities; United States